Nucleotide sequencing and an improved diagnostic for screening okra (Abelmoschus esculentus L.) genotypes for resistance to a newly described begomovirus in India. Issue 2 (3rd March 2016) - Venkataravanappa, V.; Reddy, C. N. L.; Chauhan, N. S.; Singh, B.; Sanwal, S. K.; Reddy, M. Krishna
ABSTRACT: Ten okra ( Abelmoschus esculentus L.) plants showing distinct yellow vein mosaic disease (YVMD) symptoms were collected from different fields in Karnataka State, India. The genomic DNA of the isolated viruses was amplified, cloned, and sequenced. Sequence analysis revealed that the DNA-A-like sequences of all ten isolates were identical. Sequence analysis of a representative virus isolate (OYSK2) with other begomovirus sequences available in GenBank showed ≥90% sequence identity with Bhendi yellow vein Maharashtra virus (BYVMaV; EU482411) and ≤89% homology with full-length Bhendi yellow vein mosaic virus (BYVMV) infecting okra on the Indian subcontinent. These results suggested that a new strain of BYVMaV was present in all ten samples collected from the field. A source of resistance to BYVMaV and naturally present virus isolates causing YVMD was identified by screening okra genotypes under artificial and natural inoculation conditions, respectively. None of the genotypes tested showed complete immunity to BYVMaV. However, the okra genotypes 'Tulasi' and 'Trisha' were only moderately susceptible under glasshouse and field conditions. The new begomovirus strain could be detected by dot-blot hybridisation using a non-radioactive DNA probe in the virus samples collected from both symptomless and symptomatic okra plants.